Digital Age MSME Empowerment: Synergy of Online Marketing and Capital Solutions in Cilembu Village, Pamulihan District - Hamid, Abdul; Komarudin, Udin; Purwanti, Neli (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Â Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, but still face significant obstacles, especially in the aspects of digital marketing and access to capital. This research aims to empower MSMEs in Cilembu Village, Dusun Pangkalan, through the synergy of digital marketing and financial literacy training. The implementation method includes observation, interviews, invitation distribution, and organising sharing session activities attended by 11 MSME players in the field of processed food production. The materials provided included the utilisation of social media, digital promotion content creation, preparation of financial statements, and understanding of financing access procedures, including People's Business Credit from Islamic banking institutions. The results showed a significant increase in participants' understanding of digital marketing strategies and business financial management. The participants became more confident in promoting their products online and were able to prepare simple financial statements independently. This activity proves that targeted education-based interventions can increase the capacity of MSME actors in optimising business potential and expanding market reach in the digital economy era.